2015
DOI: 10.11113/jt.v77.6446
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainability of Open Space’s Planning and Management in Nigeria: The Role of Science and Technology

Abstract: The challenges associated with integrating technology to achieve an efficient sustainability in environmental planning, and management has been the utmost concern of the researchers and professionals in built environment globally.  This has  equally  been a major issue among the environmentalists and allied professionals  in developing countries such as Nigeria. Consequently, this paper  relied on  extensive literature search through published books, journals, and periodicals.  It  critically explores the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For instance, a past study in Australian sought to address ecological sustainability, and multiculturalism by focusing on people's sense of belonging and attachment to a particular place (Cameron et al, 2004). The study's findings indicated that people' attachment to the community was a useful principle that could enhance community development and sustainability, which was equally supported by Agboola et al, (2015b). According to O'Brien and Ayidiya's (1991) residents' personal characteristics often time affect people perception on their neighbourhoods, while Cohrun (1994) opined that the membership aspect of the sense of community happened to be a major contributor to an individual's attachment to a neighbourhood.…”
Section: Residents' Attachment To the Market Squarementioning
confidence: 58%
“…For instance, a past study in Australian sought to address ecological sustainability, and multiculturalism by focusing on people's sense of belonging and attachment to a particular place (Cameron et al, 2004). The study's findings indicated that people' attachment to the community was a useful principle that could enhance community development and sustainability, which was equally supported by Agboola et al, (2015b). According to O'Brien and Ayidiya's (1991) residents' personal characteristics often time affect people perception on their neighbourhoods, while Cohrun (1994) opined that the membership aspect of the sense of community happened to be a major contributor to an individual's attachment to a neighbourhood.…”
Section: Residents' Attachment To the Market Squarementioning
confidence: 58%
“…This was corroborated by the previous studies of Mutiara &Isami, 2012 andIbrahim, Omar &Mohamad, 2013). The finding affirmed that the affordance of opportunities for social interaction in the market square would promote human needs which are essential to the psychological development of individuals and community sustainability (Berkowitz, 1996 andAgboola, Zango &Zakka, 2015). Likewise, the residents' urge to use the market square encourages being parts of the community and helps to develop and promoting residents' well-being, self-identity and communal activities ( Bryne &Wolch, 2009 andSaid, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…Plethora of literature established that local public space's interpretations are anticipated by preferred and activities emanated through the user's connection drives. The contribution of user's personal views manifests in a person's character, qualities, and necessities for human and place sustainability (Kyle et al 2004;Agboola et al 2015;Agboola et al 2014).…”
Section: Measurement Of Perception Towards the Marketplacementioning
confidence: 99%